A functional variant at the miRNA binding site in E2F1 gene is associated with risk and tumor HPV16 status of oropharynx squamous cell carcinoma. Issue 3 (20th October 2016) - Yuan, Ying; Sturgis, Erich M.; Zhu, Lijun; Lu, Meixia; Li, Yuncheng; Wei, Qingyi; Li, Guojun
Abstract : Human papillomavirus (HPV) activates E2F1 ‐driven transcription via the E7‐RB1‐E2F pathway. Genetic polymorphisms in the 3′ untranslated region (UTR) targeted by miRNAs can affect the regulation of target genes and individual cancer risk. Thus, we hypothesized that a polymorphism at the 3′UTR miRNA binding site of E2F1 gene (rs3213180) was associated with risk of oral squamous cell carcinoma (OSCC) and tumor HPV status of oropharynx squamous cell carcinoma (OPSCC). We determined the E2F1 rs3213180 polymorphism and HPV16 L1 serology of 325 OSCC patients and 335 controls, and tumor HPV16 status of 552 OPSCC. Logistic regression models were used to calculate associations of E2F1 rs3213180 polymorphism with risk of HPV‐associated OSCC and tumor HPV status of OPSCC. The risk of HPV‐associated OSCC was modified by the E2F1 rs3213180 polymorphism. Patients with both HPV seropositivity and the Ins/Del or Ins/Ins genotype of E2F1 rs3213180 had the highest risk of OSCC, while the lowest risk was detected in patients with HPV seronegativity and the Del/Del genotype. A similar and more prominent effect was detected in OPSCC, but not in oral cavity squamous cell carcinoma (OCSCC) patients. Notably, that effect trend was pronounced in never‐smokers and never‐drinkers. Furthermore, the patients with the E2F1 rs3213180 Ins/Del or Ins/Ins genotype were 2.9 times more likely to have HPV‐positive tumors than those with the Del/Del genotype. Our results suggest that the E2F1 rs3213180 polymorphism may influence susceptibility to HPV‐associated OSCC, particularly for OPSCC, never‐smokers and never‐drinkers, but not for patients with OCSCC. Additional larger population and functional studies are warranted to confirm our findings. © 2016 Wiley Periodicals, Inc.